Therapeutic Potential of Mitragyna speciosa in Neuropathic Pain and Neurodegenerative Disorders: A Literature Review - Alfan Adika Rahman; Yogi Ertanto (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
Kratom (Mitragyna speciosa) contains active alkaloids, primarily mitragynine and 7-hydroxymitragynine, which interact with the opioid, adrenergic, serotonergic, and cannabinoid systems. This review assesses primary evidence from 2020–2025 regarding neuropathic pain, cognitive or neurodegenerative effects, and pharmacokinetics and drug interactions. Three structured searches were conducted in PubMed/MEDLINE on June 16, 2026, yielding 90 records. After removing seven duplicates, 83 unique records were screened. A total of 29 reports were further assessed, and 17 primary studies met criteria. Citation and title searches added four reports, three of which met criteria, for a total of 20 studies. The evidence for pain comes primarily from animal models of chemotherapy-induced neuropathy and suggests that mitragynine may reduce allodynia through adrenergic, opioid, and cannabinoid mechanisms. Human evidence for analgesic effectiveness is observational and does not prove causality. In the cognitive domain, preclinical findings more frequently indicate impairments in learning, memory, and hippocampal plasticity with high-dose or prolonged exposure. Its therapeutic potential against Alzheimer's disease is supported by docking, in vitro AChE inhibition, and network pharmacology. Human pharmacokinetic studies indicate prolonged mitragynine exposure and potential interactions via CYP3A, while preliminary single-dose clinical data demonstrate short-term tolerability but do not yet address the safety of chronic use. Overall, kratom has consistent preclinical analgesic signals, but clinical evidence for therapeutic use in neuropathic pain and neurodegenerative disorders remains inadequate.